Security cam doesn't scrimp on the features D-LINK DSC-2121. - Oliveros, Luis Anthony G. (PC World Philippines)
It's full featured for a midrange security device, with both Ethernet and wireless capabilities and a nice management application system. A great choice if you're looking to purchase a surveillance cam, especially at its price point.